SCSS-02. INVOLVEMENT OF SUPPORTIVE CARE TEAM AND SOCIAL WORK IN NEUROONCOLOGY IN A TERTIARY CARE HOSPITAL. (21st September 2021) - Puri, Sushant; Huber, Michael; Tuite, Jason; Arzbaecher, Jean; Nicholas, Martin; Maraka, Stefania
Abstract: BACKGROUND/OBJECTIVES: Supportive Care and Social Work services are underutilized in Neurooncology. ASCO Quality Oncology Program Initiative (QOPI) includes emotional assessment by second and advance care planning (ACP) by third oncologic visit in solid malignancies. We looked (1) reason, location, and the duration from diagnosis for the involvement of supportive care teams and (2) what are the determining factors for advanced care planning in glioblastoma. METHODS: After obtaining an IRB approval for the study, we performed a retrospective chart review of glioblastoma patients seen at University of Illinois Chicago 2015-2020 using the ICD Code C71.9 for malignant gliomas. Patients who had a pathologic diagnosis of glioblastoma, age > 18 years, and had their entire neurooncologic care at UIC were included in the study. Demographic features, socioeconomic determinants, tumor characteristics, and treatment history were noted. Supportive Care Teams and Social Work notes were reviewed. RESULTS: Out of the total 403 patients, there were 78 glioblastoma patients. A total 33 met the inclusion criteria. 10 out of 33 had been seen by the supportive care team. Patients in both groups were equally matched for demographics, socioeconomic determinants, and tumor characteristics. ACP were significantly better documented in the supportive care group (p = 0.035). Supportive Care teams were consulted much later after the disease diagnosis, usually in the inpatient setting mostly consulted for goals of care discussion and hospice enrollment. There was a significant positive correlation between the involvement of Supportive Care team and Social Work. DISCUSSION: A multidisciplinary clinic including an inbuilt palliative and social work teams can improve the Quality of Life (QoL) in glioblastoma patients and their caregivers. ICD code 99497 for a dedicated ACP discussion by the neurooncologist can be used. An ongoing phase III RCT EPCOG aims to assess (QoL) in patients with glioblastoma receiving early palliative intervention.